PENGARUH PERSONAL SELLING TERHADAP KEPUTUSAN PEMBELIAN PRODUK KUE (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2024)
In a market that is increasingly competitive and influenced by ongoing technological developments, companies are required to develop effective marketing strategies to achieve their goals, including creating value and satisfying customer needs. One of the pioneers in the dessert box industry in Indonesia is Bittersweet by Najla, renowned for its innovation in presenting sweet treats in box form. This study aims to investigate the influence of personal selling on purchasing decisions of products from Bittersweet By Najla. The study employs a quantitative method by collecting information from primary and secondary sources through questionnaires and literature studies. This research uses a multiple linear regression analysis model as the research method. The population studied consists of residents in the vicinity who have made purchases at Bittersweet By Najla, with a sample of 50 respondents selected incidentally through a Likert scale-based questionnaire. Partial analysis results indicate that personal selling has a positive and significant impact on purchase decisions, supported by a significant t-value (4.012 > 1.677) and low statistical significance (0.000 < 0.05). These findings provide valuable insights for companies in designing more efficient marketing strategies, emphasizing the development of personal selling skills to enhance product appeal, build consumer trust, and achieve desired marketing objectives.
Keywords: analysis; personal selling; purchase decisions